FACTORS INFLUENCING HEALTH CARE PROVIDER IN CODUNCTING PREECLAMPSIA SCREENING - Iflah Aninda; Laksana, Muhammad Ardian Cahya; Wittiarika, Ivon Diah (UNIVERSITAS AIRLANGGA, 2024)
Background: Preeclampsia is responsible for maternal health globally due to its high morbidity and maternal mortality rates, especially in low-income countries such as Indonesia. Primary care providers, including general practitioners, midwives, and nurses, have a crucial role to play in the early assessment of preeclampsia screening. It was noted that factors affecting mortality were the lack of preparedness of officers in managing and responding to pregnancy emergencies, delayed recognition of worsening clinical signs of preeclampsia, as well as inadequate assessment and treatment for preeclampsia. This study aims to analyze the driving factors that influence health care provider in conducting preeclampsia screening in Gresik District. Methods: This research was an observational analytical study with a cross-sectional approach. The population in this study consisted of all doctors and midwives at the primary health facilities in the Gresik Regency area. The sample was taken from 159 respondents who were service providers in 20 primary health facilities in Gresik using simple random sampling. The variables in this study were the knowledge and attitudes of healthcare workers toward implementing preeclampsia screening. Data collection in this study used an online questionnaire conducted after issuing the Ethical Approval Letter until October 2023, which was then analyzed using a chi-square test with a significance level of 0.05. Results: Only 27% of respondents demonstrated a good level of knowledge about preeclampsia, which affected the effectiveness of preeclampsia screening (p-value 0.04). A total of 86.2% of respondents showed a high level of attitude toward preeclampsia screening. However, this study found no significant relationship between healthcare workers' attitudes and preeclampsia screening (p-value 0.171). Conclusion: There is a significant link between the knowledge of the healthcare provider and the optimization of preeclampsia screening so new methods of training are needed that are assessed as effective and accompanied by rigorous monitoring and evaluation to enhance healthcare provider knowledge, especially concerning preeclampsia screening.